2022
DOI: 10.3390/ani12050575
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex Cytokine Analyses in Ear Canals of Dogs Suggest Involvement of IL-8 Chemokine in Atopic Otitis and Otodectic Mange—Preliminary Results

Abstract: Cutaneous cytokines and chemokines are involved in the pathogenesis of human and canine atopic dermatitis. The aim of the present study was to discriminate cytokine expression in the ear canals of atopic dogs with otitis, dogs with non-allergic inflammatory otitis (otodectic mange) and healthy non-atopic dogs. The ear canals of nine atopic dogs suffering from non-infected otitis externa (n = 14 ears), 10 healthy dogs suffering from otodectic mange (n = 20 ears) and 21 healthy controls (39 ears) were swabbed. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 38 publications
0
7
1
Order By: Relevance
“…However, in this study, no significant increases in these cytokines were observed in the dogs with ceruminous Malassezia OE; specifically, IL-6 was barely detected in these samples. A previous study using the Luminex ® assay demonstrated that IL-6 was undetectable in the ear canal of dogs with atopic OE (6). In contrast, this study showed significantly increased concentrations of IL-1ß and IL-6 in the cerumen of dogs with suppurative bacterial OE.…”
Section: Discussioncontrasting
confidence: 70%
See 3 more Smart Citations
“…However, in this study, no significant increases in these cytokines were observed in the dogs with ceruminous Malassezia OE; specifically, IL-6 was barely detected in these samples. A previous study using the Luminex ® assay demonstrated that IL-6 was undetectable in the ear canal of dogs with atopic OE (6). In contrast, this study showed significantly increased concentrations of IL-1ß and IL-6 in the cerumen of dogs with suppurative bacterial OE.…”
Section: Discussioncontrasting
confidence: 70%
“…In an analysis of cytokine expression in conjunctival swabs, IL-8 was the only cytokine that was significantly increased in atopic dogs, showing a positive correlation with conjunctival and pruritus scores (7). In addition, the concentration of IL-8 is also significantly higher in the ears of atopic dogs than in healthy dogs (6). Interestingly, in contrast to the present study, the previous study only selected non-infected otitis patients to avoid the production of pro-inflammatory cytokines related to microbes.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…A study conducted in 2022 demonstrated the presence of inflammatory biomarkers in atopic otitis in dogs, particularly the chemokine IL-8 [27]. Unlike on the skin, inflammatory biomarkers have never been identified in the ear canals of atopic dogs.…”
Section: Variablementioning
confidence: 99%